The Influence of Tax Planning, Profitability and Liquidity on Financial Performance with Tax Amnesty as a Moderating Variable : ( Consumer Goods Industrial Sector Manufacturing Companies Classification for 2021 Listed on the Indonesian Stock Exchange for the 2016-2021 Period) - Sri Widyastuti (Economics and Digital Business Review, 2024)
Taxes are included in contributions that must and are often seen as a burden for every individual or business entity. Business entities can minimize the burden that arises from these taxes through the tax planning process. One method in tax planning is to apply a tax amnesty. This method is expected to minimize the burden and optimize the level of profits and financial performance. With optimal profits, financial performance can increase so that the company can run well and do not have to carry out tax amnesty and avoid company liquidity. This research uses secondary data obtained from the Indonesia Stock Exchange and the sample in this study is 30 Consumer Goods Industrial Manufacturing Companies using purposive sampling method. Profitability research results have a positive effect on financial performance, tax amnesty can strengthen the influence of profitability on financial performance and asset management control variables have a positive effect on financial performance. While other variables have no significant effect.